Moderating effects of intervention programs on the relationship between psychosocial factors and intention to seek treatment among Vesicovaginal fistula women in north-west Nigeria. - Nasiru, Muhammad Anka (2018)
Vesicovaginal fistula (VVF) is a childbirth disease that causes involuntary leakage of urine, and physical, social and psychological consequences for the affected women, In the past few years, the Nigerian government has implemented several intervention programs aimed at increasing the participation of treatment among the VVF women, In spite of the effort by the government to motivate the affected women to participate in the cure of the disease, the number of the victims who seek treatment is not encouraging. Previous studies have not been able to incorporate an appropriate intervention program as well as assess its suitability in interacting with psychosocial factors to increase the participation of VVF women in treatment, especially in northwest Nigeria. The primary objective of this study is, therefore, to assess the moderating effects of intervention programs on the relationships between psychosocial factors and intention to seek treatment among VVF women in northwest Nigeria. This study adopts mixed methods, and uses Partial Least Square (PLS) and Nvivo 11 software for analysis of the data. A total of 321 questionnaires was administered, 302 were valid for further analysis. In addition, an in-depth interview was conducted with nine respondents to validate the quantitative findings. The result of this study shows that there was significant association between psychosocial factors and intention to seek treatment In addition, the result of the moderating effects shows intervention programs, strengthen the relationships between attitude and intention to seek treatment, subjective norm and intention to seek treatment, and between perceived behavioral control and intention to seek treatment Thus, the study's finding shows that effective intervention programs, including rehabilitation and campaign, encourage the VVF women to participate in treatment. In addition, the study indicates that adequate funding and training of staff among others help to improve the delivery of intervention programs to the target recipients. Therefore, this study recommends that eradicating VVF disease should be made a higher priority by the policymakers and health administrators through focusing attention to improve the rehabilitation and campaign programs elements, quality of health of the citizenry, transportation, and gender equality.